2007
DOI: 10.1002/ijc.22512
|View full text |Cite
|
Sign up to set email alerts
|

The increased expression of Y box‐binding protein 1 in melanoma stimulates proliferation and tumor invasion, antagonizes apoptosis and enhances chemoresistance

Abstract: In previous studies we identified the transcription/translation factor Y-box-binding protein (YB-1) as a gene that is upregulated in primary melanoma and melanoma metastases when compared to benign melanocytic nevi. To analyze whether YB-1 expression correlates with melanoma progression in vitro and in vivo, we performed expression analysis on melanoma cell lines representing different stages of melanoma progression and on tissues of melanocytic nevi, primary melanoma and melanoma metastases. Our data indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
112
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(120 citation statements)
references
References 47 publications
6
112
0
Order By: Relevance
“…These include PIASy [56], Tip60 [56,57], Y box-binding protein 1 [58,59], p63 [60], and p73 [61]. Both p63 and p73 are rarely mutated in human cancer.…”
Section: Preventing Other Mechanisms From Inactivating P53mentioning
confidence: 99%
“…These include PIASy [56], Tip60 [56,57], Y box-binding protein 1 [58,59], p63 [60], and p73 [61]. Both p63 and p73 are rarely mutated in human cancer.…”
Section: Preventing Other Mechanisms From Inactivating P53mentioning
confidence: 99%
“…Organotypic skin reconstructs were prepared as previously described (15,16). Melanoma cells were either implemented into the fibroblast containing dermal layer (as spheroids) or seeded together with the keratinocytes as an epidermal layer.…”
Section: Organotypic Skin Culturementioning
confidence: 99%
“…Invasion assays were performed in Boyden chambers coated with a Matrigel basement membrane matrix (BD Biocoat Matrigel invasion chambers, BD Biosciences) as previously described (15). After incubation for 20 hours at 37°C, the invaded cells were fixed and counted after cell staining with H&E or quantified using their lentiviral acquired green fluorescent protein fluorescence.…”
Section: Invasion Assaymentioning
confidence: 99%
“…A previous study reported that YBX1, which is involved in malignant transformation of melanocytes, could stimulate proliferation, survival, tumor invasion, and chemoresistance (Schittek et al, 2007). Moreover, downregulation of YBX1 was hypothesized to lead to an increased rate of apoptotic cell death and a reduced rate of proliferation.…”
Section: Discussionmentioning
confidence: 99%